Efisiensi Anggaran Belanja Pada Dinas Energi Dan Sumber Daya Mineral Provinsi Nusa Tenggara Timur - Theresia Fouk Leu; Aletha Maria Nenabu (CV. ITTC INDONESIA, 2026)
The problem in this study is that the realization of spending in 2020-2023 did not reach the setting budget that was completed and in 2021 the realization of spending declined, but did not provide an overview of how the budget efficiency at the ESDM Office during 2020-2023. The purpose of this study is to know the efficiency of the direct expenditure budget at the Department of Energy and Mineral Resources of East Nusa Tenggara Province. Data collection techniques used in this study are interviews and documentation. Data analysis techniques in this study are quantitative descriptive by using direct expenditure efficiency ratios. The results of the calculation of the ratio of direct expenditure efficiency of the NTT Provincial ESDM Office during 2020-2023 amounted to 94.88% which is included in the